1985
DOI: 10.1042/cs0680357
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cobalamin binding by liver and kidney in rat and man

Abstract: Binding of cobalamin (Cbl) was compared in liver and kidney plasma membranes prepared from rat and human tissues. Single, high-affinity, saturable (200 pmol/l), binding sites for TC II-Cbl were found in all tissues; by contrast no receptors were present for free cobalamin, for which only non-specific adsorption occurred. Binding constants for TC II-CNCbl determined for liver and kidney plasma membranes were of a similar magnitude. Mean values for Ka (litre/nmol) were 16.7 (rat liver), 18.8 (rat kidney), 8.0 (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…This suggestion may help explain why in the rat most of the absorbed Cbl is retained in the kidney [30]. In support of these observations are studies [31,32] that have suggested that in the rat, the kidney acts as a storage site for Cbl. The high levels of TC II-R expression in the intestine may help in facilitating the Cbl needs of rapidly proliferating enterocytes along the entire horizontal axis of the gut.…”
Section: Resultsmentioning
confidence: 79%
“…This suggestion may help explain why in the rat most of the absorbed Cbl is retained in the kidney [30]. In support of these observations are studies [31,32] that have suggested that in the rat, the kidney acts as a storage site for Cbl. The high levels of TC II-R expression in the intestine may help in facilitating the Cbl needs of rapidly proliferating enterocytes along the entire horizontal axis of the gut.…”
Section: Resultsmentioning
confidence: 79%